ChemInform Abstract: Copper‐Catalyzed Fluorination of 2‐Pyridyl Aryl Bromides. Issue 27 (8th July 2014) - Mu, Xin; Zhang, Hao; Chen, Pinhong; Liu, Guosheng
Abstract A novel Cu‐catalyzed fluorination of aryl bromides with AgF as fluorine source is developed.